Effect of a 5-min cold-water immersion recovery on exercise performance in the heat. Issue 6 (6th June 2008) - Peiffer, J J; Abbiss, C R; Watson, G; Nosaka, K; Laursen, P B
Abstract : Background: This study examined the effect of a 5-min cold-water immersion (14°C) recovery intervention on repeated cycling performance in the heat. Methods: 10 male cyclists performed two bouts of a 25-min constant-paced (254 (22) W) cycling session followed by a 4-km time trial in hot conditions (35°C, 40% relative humidity). The two bouts were separated by either 15 min of seated recovery in the heat (control) or the same condition with 5-min cold-water immersion (5th—10th minute), using a counterbalanced cross-over design (CP1 TT1 → CWI or CON → CP2 TT2 ). Rectal temperature was measured immediately before and after both the constant-paced sessions and 4-km timed trials. Cycling economy and Vo2 were measured during the constant-paced sessions, and the average power output and completion times were recorded for each time trial. Results: Compared with control, rectal temperature was significantly lower (0.5 (0.4)°C) in cold-water immersion before CP2 until the end of the second 4-km timed trial. However, the increase in rectal temperature (0.5 (0.2)°C) during CP2 was not significantly different between conditions. During the second 4-km timed trial, power output was significantly greater in cold-water immersion (327.9 (55.7) W) compared with control (288.0 (58.8) W), leading to a faster completion time in cold-water immersion (6.1 (0.3) min) compared with control (6.4 (0.5) min). Economy and Vo2 were not influenced by the cold-water immersion recovery intervention. Conclusion: 5-min cold-water immersion recovery significantly lowered rectal temperature and maintained endurance performance during subsequent high-intensity exercise. These data indicate that repeated exercise performance in heat may be improved when a short period of cold-water immersion is applied during the recovery period.